Prevalence of unmet need for contraception in urban slum communities, Mumbai - Begum, Shahina; Nair, Saritha; Donta, Balaiah; Prakasam, C. P. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Unmet need for family planning is a tool to monitor the family planning program. Hence, the objective of study is to examine the prevalence of unmet need for family planning among women living in urban slum communities, Mumbai. Methods: The cross-sectional survey was conducted among currently married women aged 18-39 years and having at least one child. A total of 2797 women were selected using systematic random sampling. Information on demographic characteristics, their contraceptive behaviour and fertility intention were collected by face to face interview using structured questionnaire. Chi square test was applied and p <0.05 was considered as significant. Results: About 59.4% were currently using family planning methods and 40.6% have reported unmet need for family planning. Awareness of contraceptive methods among women with unmet need for family planning was universal. The prevalence of unmet need for family planning significantly decreased as the age and number of children increased. The prevalence of unmet need was significantly higher than met need for family planning among women having one child as compared to women having 2 or more children. Conclusions: A significant gap was observed between met and unmet need for family planning among younger women and having one child. The study emphasises the need for family planning programs to focus on younger couples having one child.